ComMODify User Creativity at the Intersection of Commerce and Community - van der Graaf, Shenja (Dynamics of Virtual Work, 2018)
This book critically analyses user-firm technology relationships and socioeconomic structures at the crossroads of community and commerce. It investigates businesses that let users participate in platform development on the internet. An empirical study of the online world Second Life is used as an early illustration of the pivotal role of user participation in design, development and sustainability of digital platforms. Van der Graaf sheds light on aspects of the ongoing platformization of the internet and on new norms and mechanisms for user participation which are linked to values of creativity, community and labour. ComMODify makes clear that robust theoretical and empirical investigation of the integration of user participation into mainstream business models and its implications for platform development is key to understanding contemporary businesses like Facebook, that sustain the internet of today. This book will be of interest to those wanting to learn more about the socio-economic implications of user participation associated with user-generated content, particularly within the 3D software and game industry.